The Effect of Service Innovation on Public Satisfaction at the Office of Population and Civil Registration of Pekanbaru City - Kurnia, Dedi; Mukson, Mukson; Fuaddi, Husni (Nexus Synergy: A Business Perspective, 2024)
The purpose of this study was to determine the effect of service innovation on public satisfaction at the Population and Civil Registration Office of Pekanbaru City. The sample in this study was the community at the Population and Civil Registration Office of Pekanbaru City totaling 100 people. The data analysis used was validity test, reliability test, normality test, heteroscedasticity test, simple linear regression, determination coefficient test and partial test (t test). Based on the results of the study, it is known that the determination coefficient of the Service Innovation variable as a whole has an influence of 57.5% on Public Satisfaction while the remaining 42.5% is influenced by other factors not studied by the author. The results of the hypothesis test show t count (11,514)> t table (1.984) with sig 0.000 <sig 0.05, so it can be concluded that there is a significant influence on Service Innovation on Public Satisfaction at the Population and Civil Registration Office of Pekanbaru City.